Assessing Acceptance Toward Wiki Technology in the Context of Higher Education - Altanopoulou, Panagiota; Tselios, Nikolaos (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This study investigated undergraduate students’ intention to use wiki technology. An extension of the Technology Acceptance Model (TAM) has been used by taking into account not only students’ wiki perceived utility and usability, but also Big Five personality characteristics and two other variables, social norms, and facilitating conditions, as proposed in the Unified Theory of Acceptance and Use of Technology (UTAUT). Students’ beliefs before (pre-wiki scenario) and after (post-wiki scenario) the actual use of the wiki system were investigated, with 85 and 86 participants respectively. The hypotheses were tested using partial least squares analysis. For the pre-wiki scenario, 8/15 hypotheses were confirmed and 11/15 for the post-wiki scenario. The relationship between perceived ease of use and perceived usefulness was found to be of the highest magnitude. The most notable difference across the two scenarios was that the relation between perceived ease of use and attitudes towards use was significant only in the first scenario. The results demonstrate that the proposed TAM-extended model could predict students’ wiki acceptance.